Experimental evolution of cellular miniaturization reveals a putative mechanism for cell size evolution - Ana Garoña; Morgane V. Lemos; Andrea Giometto; Marco Fumasoni (Proceedings of the National Academy of Sciences, 2026)
Cell volume, a key determinant of physiology, is maintained by cell size homeostasis. Large deviations from typical size are often harmful, yet cell sizes have diverged drastically during evolution. How size homeostasis evolves to support such diversity without impairing cellular function remains unclear. To address this question, we used experimental evolution to progressively select for smaller Saccharomyces cerevisiae cells. Over 1,500 generations, we achieved a fourfold modal volume reduction compared to wild type. Despite this reduction, evolved populations maintained robust size homeostasis and relatively high fitness, revealing that substantial decreases in cell volume can occur without severe growth defects. Whole-genome sequencing and genetic perturbations identified mutations in the G1 cyclin Cln3 and the Target of Rapamycin (TOR) pathway effector Sch9 as major contributors to cell size reduction, with the Greatwall kinase Rim15 signaling cascade further modulating this phenotype. Manipulating these pathways produced a sixfold range in cell size without changes in ploidy, with engineered mutations recapitulating the volumes of evolved lines, and loss-of-function mutations yielding enlarged cells. Our results demonstrate the evolutionary plasticity of cell size homeostasis and reveal a putative mechanism for eukaryotic cell size evolution.